Glancing angle intermediate layer deposition approach for CVD diamond coating of high-speed steel substrates; Surfaces and Interfaces; Vol. 45 - Gaydaychuk A. V. Alexander Valerievich; Linnik S. A. Stepan Andreevich; Mitulinsky A. S. Aleksandr Sergeevich; Bulakh V. A. Vlada Aleksandrovna; Zenkin S. P. Sergey Petrovich (2024, 2024)
Title screen